“MBLANDONG” UNTUK MENOPANG PEREKONOMIAN MASYARAKAT PINGGIR HUTAN : SUATU PENDEKATAN HISTORIS ANTROPOLOGIS (Kasus : Di Desa Kawengen Kabupaten Semarang) - Eko Punto Hendro (Studi Budaya Nusantara, 2019)
In the people of Kawengen Village, “mblandong” is  the best economy activity. They have ignored legal or illegal rules, because at the reality, mblandong can develop of the other sector of economy at their village, to the agriculture, carbon industies, industries of handicraft and furniture. Beside that, mblandong also can available to the building material. In this case, mblandong very important for economic, and than mblandong will be custom or folkways of The Kawengen people.